The Effect of Node Speed on Mobile Ad Hoc Network Performance - Abdelsalam Abdelhamid Almarimi; Faraj Abdulaziz; Adel Elashheb (International Journal of Applied Methods in Electronics and Computers, 2016)
Announcement between mobile nodes is a challenging network especially via Mobile Ad hoc Network (MANET), where mobile nodes are capable of moving on a continual basis, which is changeable and challenging to analyse the performance of its routing protocols and application. In this paper, we evaluate the performance of routing protocols over MANET for Ad Hoc on demand Distance Vector (AODV), Destination-Sequenced Distance Vector (DSDV), as well as Dynamic Source Routing (DSR). We use Network Simulator NS-allinone-2.31 tool for the practical testing and evaluation. We have tested the routing protocols AODV, DSDV, and DSR. So, different performance features are investigated including , Packet loss,  Packet Delivery Fraction (PDF), End-to-End Delay. The results indicate that performance of routing protocols where the number of nodes  start from 5 to 100 nodes during the entire scenario for node speeds equivalents to 10m/s, besides the delivery of packet size equivalents to 512kb.